Peutz-Jeghers syndrome: A case report - Poudel, Pratima; Jahan, Roushan (Asian Journal of Medical Sciences, 2021)
Peutz-jeghers syndrome is a rare inherited autosomal dominant disease which is characterized by mucocutaneous pigmentation and multiple polyps in the gastrointestinal tract. We report a case of 10 years old female who was referred to us from surgical department for the evaluation of brownish pigmented macules over lips, face, palms and soles. Patient was presented with recurrent abdominal pain along with vomiting and blood mixed stool for a month. Ultrasound of abdomen revealed jejuno-jejunal intussusception for which laparotomy was done during which multiple polyps were visualized. Polypectomy was done and biopsy revealed it to be tubulovillous adenoma. Patient was diagnosed as Peutz-jeghers syndrome as there were multiple polyps in the jejunum along with the characteristics mucocutaneous involvement.